Towards an Aware Society: Counseling on the Prevention of Unregistered Marriages for Students at Muqorrobin Islamic Middle School, Malang: Menuju Masyarakat Sadar: Penyuluhan Pencegahan Pernikahan Siri bagi Peserta Didik SMP Islam Muqorrobin Malang - Jannah, Shofiatul; Muslim, Moh.; Khofsah, Sholihatin (Universitas Lancang Kuning, 2024)
Analysis of the partner situation illustrates phenomena in society that many do not understand the legal consequences of serial marriages, including regarding the inheritance and legal status of children from serial marriages. The problem that arises is when there are still residents who carry out serial marriages (not recorded), and then issues arise regarding inheritance rights when the husband dies, as well as joint property rights when there is a divorce. The approach to solving partner problems is the lecture and question-and-answer method. The evaluation results showed that community understanding increased significantly after being given socialization, with evaluation accuracy reaching 98%. The purpose of this socialization is to increase the understanding of the community of SMP Islam Muqorrobin Malang regarding the legal consequences of serial marriage.